Transatlantic Russian Jewishness : ideological voyages of the Yiddish daily Forverts in the first half of the twentieth century - Ėstraĭkh, G. (Gennadiĭ) (Jews of Russia & Eastern Europe and their legacy., 2020)
"In the early decades of the twentieth century, tens of thousands of Yiddish speaking immigrants actively participated in the American Socialist and labor movement. They formed the milieu of the hugely successful daily Forverts (Forward), established in New York in April 1897. Its editorial columns and bylined articles-many of whose authors, such as Abraham Cahan and Sholem Asch, were household names at the time-both reflected and shaped the attitudes and values of the readership. Most pages of this book are focused on the newspaper's reaction to the political developments in the home country. Profound admiration of Russian literature and culture did not mitigate the writers' criticism of the czarist and Soviet regimes"--